2019
DOI: 10.1097/icl.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial to Evaluate the Effect of Toric Versus Spherical Contact Lenses on Vision and Eyestrain

Abstract: Objectives:To compare the effect of toric versus spherical soft contact lenses on objective measures of visual performance using visual acuity and electromyography of the orbicularis oculi muscle.Methods:Current soft contact lens wearers with −0.75 to −1.75 D astigmatism in each eye were binocularly fitted with toric (1-Day ACUVUE MOIST for astigmatism) and spherical (1-Day ACUVUE MOIST) contact lenses in random order. After each fitting and at 1-week follow-up, high- and low-contrast visual acuities were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Several recent studies have reported the benefit of correcting low amounts of astigmatism in comparing distance vision and near visual performance with digital devices or night-time driving performance. [30][31][32][33][34] According to a recent systematic literature review on the epidemiology and burden of astigmatism, 35 uncorrected astigmatism decreases the vision-related quality of life and work productivity, in addition to posing an economic burden on patients. Based on these results, a proactive prescription of toric CLs for eyes with astigmatism is recommended because improved visual performance and more patient satisfaction are expected when astigmatism is corrected properly.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported the benefit of correcting low amounts of astigmatism in comparing distance vision and near visual performance with digital devices or night-time driving performance. [30][31][32][33][34] According to a recent systematic literature review on the epidemiology and burden of astigmatism, 35 uncorrected astigmatism decreases the vision-related quality of life and work productivity, in addition to posing an economic burden on patients. Based on these results, a proactive prescription of toric CLs for eyes with astigmatism is recommended because improved visual performance and more patient satisfaction are expected when astigmatism is corrected properly.…”
Section: Discussionmentioning
confidence: 99%
“…In those with low to moderate amounts of astigmatism, toric CLs improve visual acuity, [206][207][208] subjective vision, 16 visual symptoms, 16 eyestrain, 207 and satisfaction 16 compared to spherical CLs. While prescribing spherical CLs to those with significant astigmatism may have been a source of vision problems in the past, 209 it does not appear to be a current source.…”
Section: Astigmatism and Toric Contact Lensesmentioning
confidence: 99%
“…Correcting low to moderate amounts of astigmatism with toric CLs can improve subjective vision, 16 visual symptoms, 16 and eyestrain, 207 compared to correction with spherical CLs. All participants in the current study wore spherical CLs, including those with up to 1.00 D of astigmatism, suggesting uncorrected astigmatism may have been a…”
Section: Potential Limitationsmentioning
confidence: 99%
“…4 This is beneficial to patients as studies indicate improved visual acuity and contrast sensitivity when fitted with toric contact lenses. [5][6][7] More recently, a study comparing subjective and objective measures of visual performance with digital devices in astigmatic patients trialing toric and spherical lenses of the same material found that participants preferred the comfort and vision with the toric contact lenses. 8 Dumbleton et al 9 investigated contact lens drop out in a retrospective sample of over 4,000 lapsed wearers, and while discomfort was cited as the most common cause, poor vision and issues with lens handling were also common causes of lens discontinuation.…”
mentioning
confidence: 99%
“… 4 This is beneficial to patients as studies indicate improved visual acuity and contrast sensitivity when fitted with toric contact lenses. 5 7 More recently, a study comparing subjective and objective measures of visual performance with digital devices in astigmatic patients trialing toric and spherical lenses of the same material found that participants preferred the comfort and vision with the toric contact lenses. 8 …”
mentioning
confidence: 99%